The Assistance Of Digital Marketing As Marketing Strategy Of Catfish Cultivation Business In Sidakarya Village - Ni Made Rini Darmayanti; Kadek Devi Kalfika Anggria Wardani; Gusi Putu Lestara Permana (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
With the COVID-19 outbreak that has hit the whole world, many economic sectors have declined and have suffered a lot of losses, even in Indonesia itself is still trying hard to restore the domestic economy by imposing restrictions on all areas of the islands of Java and Bali. One of the businesses affected is Catfish Cultivation in Sidakarya Village, therefore socialization and training are needed regarding improving business management through the use of digital marketing technology. The purpose of this service activity is to increase knowledge and awareness as well as innovate business managers to increase sales, market crops and foster good relationships with consumers. The methods used are (1) initial & planning stages; (2) the implementation stage of making ; (3) the stage of mentoring (monitoring); (4) evaluation & final stage. Providing socialization and understanding education to business managers regarding online media and business location information media that are currently trending and can be used as a medium in marketing products in the midst of the Covid-19 pandemic as an effort to handle problems that are currently happening in the village catfish farming business. Sidakarya. The results of this activity are the creation of social media accounts and google maps, logo design and product upload templates.